2011
DOI: 10.1021/mp2001395
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Release of Metformin HCl through Incorporation into Stomach Specific Floating Alginate Beads

Abstract: The aim of present study was to develop stomach specific floating beads of metformin hydrochloride for effective management of type 2 diabetes mellitus. The beads were evaluated for surface morphology, particle size, tapped density, true density, percent porosity, drug entrapment efficiency, percent yield, differential scanning calorimetry, in vitro floating ability and in vitro drug release. Stability studies were performed at 25 and 40 °C up to 45 days. Effectiveness of the formulations was evaluated in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
4
19
1
Order By: Relevance
“…It was observed that the degree of swelling of AL beads increased with increase of pH of release medium, probably due to exchange of the Ca 2+ ion with Na + . These results are in agreement with the results of previous studies [11,15]. Various approaches (chemicals, dietary manipulation, or surgery) are available in the literature for development of experimentallyinduced type 2 diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It was observed that the degree of swelling of AL beads increased with increase of pH of release medium, probably due to exchange of the Ca 2+ ion with Na + . These results are in agreement with the results of previous studies [11,15]. Various approaches (chemicals, dietary manipulation, or surgery) are available in the literature for development of experimentallyinduced type 2 diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the fasting blood glucose levels of metformin HCl-loaded AL-CS and AL beads gradually declined and peaked in 6 hr and 4 hr, respectively, indicating that hypoglycaemic effect was extended by both bead formulations. Similar observations are reported in the literature [15,32]. Nayak et al [15] evaluated the hypoglycaemic effects of nonfloating and floating alginate beads containing metformin HCl on STZ-induced diabetic rats and found that a significant hypoglycaemic effect was obtained for floating beads 3 to 9 hr after bead administration.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations